The use of digital ICT by teachers and their adaptation to current models - Flores-Tena, María José; Ortega-Navas, María del Carmen; Sousa-Reis, Carlos (Revista Electrónica Educare, 2021)
In the article we present a study in which it is intended to verify the importance and adequacy of the use of information and communication technologies (ICT) in the school environment for its greater adaptation to reality. This question is reflected in the general objective of the same, which focused on determining the use that teachers make of new technologies in the classroom and their impact on the teaching-learning process of their students, taking into account the current weaknesses. on the pedagogical bases used by some of the most recent studies on the use and optimization of digital ICT in the classroom. The study is framed in a quantitative, non-experimental, descriptive and correlational design. 100 teachers of Compulsory Secondary Education (ESO) from institutes of Coimbra (Portugal) participated in the study. An ad hoc questionnaire was developed to discover the use and frequency of new technologies in the classroom by teachers. The data collected in the questionnaires were analyzed using the statistical package Statistical Package for the Social Sciences. The main conclusions confirm that there is still a need for an in-depth debate on the epistemological foundations implicit in the use of new digital tools on whether ICT, as an appropriate teaching tool, according to current educational models, in terms of time-cost for better student performance and academic success. In fact, the debate is more than ever alive, new technologies were increasingly inserted in the educational field, during COVID-19, which also implied the suspension of classroom teaching activities that led to the use of new technologies in the classroom. class immediately.